2020
DOI: 10.1093/ptj/pzz090
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise on Cancer-Related Cognitive Impairment and Applications for Physical Therapy: Systematic Review of Randomized Controlled Trials

Abstract: Background Cancer-related cognitive impairment (CRCI), often called “chemo-brain” or “chemo-fog,” is a common side effect among adults with cancer, which can persist well after treatment completion. Accumulating evidence demonstrates exercise can improve cognitive function in healthy older adults and adults with cognitive impairments, suggesting exercise may play a role in managing CRCI. Purpose The purpose was to perform a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 71 publications
2
76
0
2
Order By: Relevance
“…However, many of these studies have methodological limitations related to study design (i.e., observational, lack of comparison group, small sample size, short duration of follow-up). A particular shortcoming of published studies concerns the approach used to assess cognitive functioning (i.e., reliance on self-report measures, assessment of cognitive functioning as a secondary outcome, using a single item or a subscale of a questionnaire assessing fatigue or quality of life [ 40 ]). Only two published aerobic exercise RCTs have evaluated cognitive functioning as the primary outcome: one in women receiving chemotherapy for breast cancer [ 45 ], the other in women who completed chemotherapy for breast cancer [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many of these studies have methodological limitations related to study design (i.e., observational, lack of comparison group, small sample size, short duration of follow-up). A particular shortcoming of published studies concerns the approach used to assess cognitive functioning (i.e., reliance on self-report measures, assessment of cognitive functioning as a secondary outcome, using a single item or a subscale of a questionnaire assessing fatigue or quality of life [ 40 ]). Only two published aerobic exercise RCTs have evaluated cognitive functioning as the primary outcome: one in women receiving chemotherapy for breast cancer [ 45 ], the other in women who completed chemotherapy for breast cancer [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential of exercise to improve CRCC is unclear. A recent systematic review of 29 published randomized controlled trials (RCTs) found limited evidence for the benefit of exercise compared to usual care on CRCC in adults diagnosed with cancer, including those diagnosed with breast cancer [ 40 ]. Three RCTs in women receiving chemotherapy for breast cancer reported a statistically significant effect of aerobic exercise on CRCC, as measured by performance-based neuropsychological tests (i.e., objective measures [ 41 ] and self-report questionnaires [ 41 – 43 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various interventions for cancer‐related fatigue have been proposed, ranging from counseling‐based therapy to pharmacotherapy (eg, corticosteroids, methylphenidate), but none have produced a definitive benefit in this patient population. Some evidence suggests that mindfulness techniques and exercise may benefit patients, but available data indicate that benefits are modest and inconsistent 286 …”
Section: Survivorship and Patient Resiliencementioning
confidence: 99%
“…These 12 trials used the EORTC QLQ-C30 exam for cognitive functioning. In 10 other trials (34%), neuropsychological testing was used to evaluate cognitive functioning; however, only 3 of these trials in breast cancer reported significant benefits from exercise (Cohen d range: 0.41–1.47) [ 17 ].…”
Section: CI In Cancer Patientsmentioning
confidence: 99%